PENGEMBANGAN MODUL STATIC STRUCTURAL BERBASIS EXPERIENTIAL LEARNING MENGGUNAKAN FINITE ELEMENT METHOD PADA MATA KULIAH BAHAN TEKNIK - Ilyasa, Muhammad Nabil; Ihwanudin, M; Sumarli, Sumarli (Universitas Negeri Yogyakarta, 2024)
AbstractThe problem in the Engineering Materials class is that students still consider the Engineering Materials course to be material that is difficult to understand. With these problems, this research aims to develop the